2010
DOI: 10.2147/idr.s7641
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus in HIV-infected patients

Abstract: Concordant with the emergence of methicillin-resistant Staphylococcus aureus (MRSA) in the community setting, colonization and infections with this pathogen have become a prevalent problem among the human immunodeficiency virus (HIV)-positive population. A variety of different host- and, possibly, pathogen-related factors may play a role in explaining the increased prevalence and incidence observed. In this article, we review pathophysiology, epidemiology, clinical manifestations, and treatment of MRSA in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 148 publications
(265 reference statements)
6
64
0
2
Order By: Relevance
“…HIV infected patients are recognized as one of these higher risks groups due to increased rates of both MRSA colonization and infection [11]. The organism's interactions and disease manifestations with the immunocompromised host are expected to be complex and involve defects in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV infected patients are recognized as one of these higher risks groups due to increased rates of both MRSA colonization and infection [11]. The organism's interactions and disease manifestations with the immunocompromised host are expected to be complex and involve defects in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The organism's interactions and disease manifestations with the immunocompromised host are expected to be complex and involve defects in innate immunity. Chemo taxis, neutrophil phagocytosis and intracellular killing are vital steps in host defense against S. aureus [11]. Some studies showed significant dysfunctions concerning these elements in persons with HIV [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tuberculosis (TB) and methicillin-resistant Staphylococcus aureus (MRSA). [2][3][4] MRSA co-infection is characterized by a high incidence rate. 5 In addition, the emergence of multidrug resistant MRSA markedly increased among HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus has emerged as a significant opportunistic pathogen among HIV and AIDS patients in both nosocomial and community settings, and recent studies have shown greater frequency and morbidity of this organism among HIV positive individuals (Chacko et al, 2009., Hidron et al, 2010). Clinical manifestations ranged from superficial to systemic disease conditions, responsible for high morbidity and mortality rate (Lowry et al, 1998).…”
Section: Introductionmentioning
confidence: 99%